PENERAPAN MODEL CREATIVE PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA KELAS V SDI WAE CIU, KECAMATAN LAMBA LEDA UTARA, KABUPATEN MANGGARAI TIMUR - Tika Sriwahyu Ningsih; Heronimus E.A. Wejang; Ambros Leonangung Edu (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2022)
This research was motivated by the problem of students’ learning outcomes at SDI Wae Ciu becaused of the use of conventional learning models. The purpose of the study was to describe the comparison of student learning outcomes through the use of the Creative Problem Solving (CPS) model, and also to describe whether using the Creative Problem Solving (CPS) learning model could improve student learning outcomes. This type of research was quantitative research with experimental methods. Experimental research was causal (causation) where its evidence was obtained through comparisons between the experimental group (which was treated) through the use of the Creative Problem Solving (CPS) learning model, and the control group (which was not treated). Data collection techniques was the test to collect data on student learning outcomes. The data analysis technique used was the t-test, after testing the normality and homogeneity. The results showed that the Creative Problem Solving (CPS) model had a positive influence on student learning outcomes. Based on the results of the Paired Samples T-Test analysis, the posttest results obtained in the experimental class and control class were known that the t-count is 0.05 with a significance of 0.000. The significance value (2-tailed) which showed 0.000 > 0.05, then Ho was rejected and Ha was accepted. The Creative Problem Solving (CPS) learning model also determined the accuracy of the expected goals, learning would be effective, efficient and the expected learning outcomes would be achieved. Based on the research that has been done, there was a significant effect on improving student learning outcomes by using the Creative Problem Solving (CPS) learning model.